Strategies of persuasion in Herodotus' Histories and Genesis-Kings: evoking reality in ancient narratives of a past - Tyrell, Eva (Journal for the study of Judaism / Supplements, 2020)
"In Strategies of Persuasion in Herodotus' Histories and Genesis-Kings, Eva Tyrell comparatively analyzes narrative means in two monumental ancient texts about the past. Combining a narratological approach with insights of modern historical theory and biblical scholarship, she investigates patterns of narrative persuasion as a trans-cultural phenomenon and their connection with ancient concepts of reality and truth. The study contrasts differences in fundamental narrative structures of both narratives, such as mediacy and discursive versus diegetic text portions. It explores the role of material remains mentioned in the accounts to evoke or even create the reality of a past"--